Effect of glycemic index of pre-exercise meals on fat and carbohydrate oxidation - Choo, Jia Yi (2014)
This study investigated the effects of consuming a high or low glycemic index (GI) meal, matched for volume, on fat and carbohydrate oxidation during exercise. Five male endurance runners (age: 22.4 ± 1.1; BMI: 22.1 ± 1.1kg/m2; VO2max: 53.7 ± 5.8ml/kg/m) participated in two trials in a randomized, cross-over study, separated by at least seven days. The participants ran on the treadmill at 70% VO2max for 5km, two hours after consuming either a high (GI = 74) or low (GI = 42) GI meal. The meals consisted of 250ml of cereal and 300ml of skimmed milk, 300ml of water was also given with the meal. Results showed no significant differences for fat (high GI: 0.34 ± 0.11; low GI: 0.33 ± 0.07; p = 0.85) and carbohydrate oxidation (high GI: 2.22 ± 0.42; low GI: 2.25 ± 0.29; p = 0.83) between the two trials. In addition, no differences in heart rate (HR) (high GI: 153 ± 10.51; low GI: 155 ± 1.63; p = 0.73) and rate of perceived exertion (RPE) (high GI: 12 ± 0.82; low GI: 11 ± 0.36; p = 0.07) were found between the two trials. The lack of significant differences between the two trials could be due to the insufficient duration of the run and the exercise intensity could have been too high to elicit any disparity in substrate oxidation. In summary, consuming a high or low GI meal prior to exercise did not have any effect on fat and carbohydrate oxidation during exercise.